Aide-toi, la viralité t’aidera. Ou de la création et diffusion des proverbes dans les médias - Vincenzo Lambertini (MediAzioni)
This study aims to analyse the relationship between virality and proverbs. After defining virality and proverbs, I will take into account some examples of virality before the advent of the Internet. Thus, I will compare proverbs and virality through contrasting (French-Italian) and interdisciplinary (from biology and virology) approaches, using authentic examples drawn from social media and semi-spontaneous conversations broadcast on radio or television. This study will show not only that virality and proverbs share many features, but also that proverbs can adapt to new realities (which may allow them to evolve in the future without disappearing). Finally, this research highlights that “endemic phases” of virality deserve to be explored in depth.